Anatomising ‘Athens’: Architecture, Medicine, and the Lieux de Savoir in Early Modern Edinburgh - Ann-Marie Akehurst (Angles)
This paper contends that Edinburgh’s international reputation as a centre for intellectual excellence rested on a unique context which favoured the spread of ideas and research. Crucially, strands which coalesced were its excellence in medicine, related to other scientific enquiry; its topography, which dictated a mutual proximity in the parts of the city concerned with the advancement of such knowledge; and buildings, both ancient and modern. By using Christian Jacob’s notion of lieux de savoir, I argue Edinburgh’s identity emerged from the entanglement of lieux de mémoire and lieux de savoir. By focusing on the spaces and social activities of Edinburgh’s medical lieux de savoir this paper traces how the epistemic fields of new medicine and science influenced Edinburgh’s international reputation as an Enlightenment city. I argue that in the potting sheds of the botanical gardens, on the benches of the anatomy theatres, within the walls of Royal Colleges and the University, and between the pages of books, Ancient and Modern learning and culture was hotly debated, and the application and management of new knowledge was negotiated. Edinburgh’s lieux de savoir was a crucible forging the Enlightenment city that was projected across academic departments, and through its publications and influential alumni including surgeons on British ships, to imperial contact zones across the world.